705 Lessons learned from conducting road safety curriculum in Thai Schools - Jamjuree, Danulada; Srathongphun, Saifon (Child and Adolescent Safety, 2016)
Teaching and learning road safety has been recommended as a core strategy in both nation and international levels. In Thailand, the Ministry of Education has launched a policy to integrate road safety with school’s core curriculum since 2003. In 2006, Road Safety Safety Group Thailand(RSC) reemerged road safety curriculum to foster road safety behaviours in children. Beginning with 2 schools in Lampang Province, Northern of Thailand and the number increased later. Now 6 primary and secondary schools in Lampang manage road safety curriculum. This research focused on road safety curriculum, instructional approach, and outcomes found in 6 schools in Lampang Province.MethodsThe After Action Review(AAR) was conducted to explore lessons learned in road safety curriculum. Two studies from this curriculum are a content analysis of road safety curriculum in 6 schools and focus group discussion with stakeholders. It was conducted between December 2012 to April 2013.Results 1. Patterns of integrated road safety curriculum. Results can be described in 4 patterns: (1) themes of road safety that share contents within each subject of school’s core curriculum, (2) activities on road safety in one subject that connect to another subjects, (3) integration road safety curriculum within each subject of school’s core curriculum, and (4) mix methods of pattern 1 and 2. 2. Key success factors. (1) teacher’s knowledge and skills for integrating road safety curriculum to school’s core curriculum, (2) school’s readiness, (3) teacher’s participation and empowerment, and (4) principal’s supportive and facilitation. 3.Outcomes. Results found that most of students (1) had increased road safety skills especially in walking on the street, crossing road and using helmet, (2) had more knowledge and understanding about traffic policy, (3) the concern about wearing helmet behaviour increased from 49% to 88.7%.ConclusionsThis study shows that road safety curriculum can be done and works well with school’s core curriculum. The success of the application is depended on (1) school’s readiness, (2) knowledge and understanding of teachers to road safety curriculum and nature of road safety, (3) administrator’s policy and support, and (5) reconcile teacher’s attitude at the beginning of taking this curriculum to school.